Correlation Between the Prognosis of Sudden Total Deafness and the Peripheral Blood Inflammation Markers - Diao, Tongxiang; Ke, Yujie; Zhang, Junbo; Jing, Yuanyuan; Ma, Xin (Frontiers in Neurology, 2022)
Objective To analyze the correlation between prognosis of total deafness (TD) and peripheral blood inflammation makers including white blood cell count (WBC), monocytes, neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), fibrinogen (FIB). Methods 125 patients with TD who were hospitalized in our department from 2014 to 2019 were enrolled. The general physical conditions, clinical manifestations, pure tone audiometry, imaging examination, and peripheral blood inflammation makers were collected, and all patients were divided into effective and ineffective two groups according to the degree of hearing recovery at the time of discharge. Then binary logistic regression was used to analyze the correlation between multiple factors and prognosis , meanwhile the receiver operating characteristic (ROC) curve was used to evaluate the predictive value of the above prognostic factors. Results Compared with the ineffective group, patients in the effective group were younger and have higher PLR level and lower FIB levels. Age and PLR are independent prognostic factors. Taking age ≤ 56 years old, PLR > 142.6 as the standard to predict the prognosis of patients with TD has the largest AUC with the potential effective rate reaching 78.1%. Conclusions Age and PLR are independent prognostic factors for patients with TD. The younger the age and the higher the PLR, the better the prognosis. Clinically, the prognosis of patients with TD can be evaluated by the patient's age and PLR level, which is of great significance to predict the prognosis of patients with TD.